Análise ambiental do descarte irregular de lixo da bacia hidrográfica do Educandos, Manaus-Am - Barbosa, Emerson da Costa (2023)
The objective of this research was to carry out an environmental diagnosis of the Educandos river basin in order to identify the environmental impacts resulting from the irregular disposal of solid waste in the water system. The diagnosis was carried out based on the characterization of the study area, which included the identification of changes in river courses, the characterization of the use and occupation of urban land and, finally, field evaluations. Once this diagnosis was made, the next step was to carry out an analysis of the main impacts in the basin. This research had the importance of being part of the environmental concerns currently in vogue. It also attempts to shed light on local issues relating to weaknesses in public management in relation to the ecosystem services provided by water systems in the Educandos watershed in the urban area of ​​Manaus (AM).